Answer:
c=9
d=3
Explanation:
We have been asked:
What value of c makes x2 + 6x + c a perfect square trinomial?
c =
If x2 + 6x + c = (x + d)2, then d =
First step we have to do is divide the coefficient of x by 2. The coefficient is 6
6/2 = 3
Now take the square of 3 = 3^2
3^2 = 3*3 =9
The value of c is 9
If x^2 + 6x + c = (x + d)^2, then d =?
Put the value of c in the equation:
x^2+6x+9
Take the square root of 1st and third term. Then the expression can be written as:
x^2+6x+9 = (x+3)^2
Thus the value of d is 3.
If x^2 + 6x + 9 = (x + 3)^2, then d = 3 .....